1998
DOI: 10.2307/3284732
|View full text |Cite
|
Sign up to set email alerts
|

New Data on the Early Development of Hysterothylacium aduncum (Nematoda, Anisakidae)

Abstract: This note reports on incidental observations of the early development of the third-stage larvae of Hysterothylacium aduncum from gadid fishes. Gravid H. aduncum females were collected from Pollachius virens, Pollachius pollachius. Gadus morhua, and Molva molva in Norwegian waters. The eggs were incubated at 20 per thousand salinity and 5 C. Spontaneous hatching of third-stage larvae was observed 10-25 days after egg deposition. These larvae were long lived and could infect Acartia tonsa copepods, the infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
23
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 2 publications
(3 reference statements)
1
23
1
Order By: Relevance
“…For eggs from Week 3, these percentages were lower than 0.1%. The larvae started to hatch 23 d after deposition, a time lapse higher than the 10 d previously reported by Yoshinaga et al (1987) and Balbuena et al (1998), although these authors indicated a range of 10 to 22 or 10 to 25 d, respectively. As with the eggs, the hatched larvae also had negative buoyancy in the saline solution used, and tended to be deposited on the bottom of the culture flasks.…”
contrasting
confidence: 55%
See 4 more Smart Citations
“…For eggs from Week 3, these percentages were lower than 0.1%. The larvae started to hatch 23 d after deposition, a time lapse higher than the 10 d previously reported by Yoshinaga et al (1987) and Balbuena et al (1998), although these authors indicated a range of 10 to 22 or 10 to 25 d, respectively. As with the eggs, the hatched larvae also had negative buoyancy in the saline solution used, and tended to be deposited on the bottom of the culture flasks.…”
contrasting
confidence: 55%
“…1987, Køie 1993, Balbuena et al 1998, González 1998) may be due to the occurrence of subspecies of Hysterothylacium aduncum (Hartwich 1975, Petter & Cabaret 1995. It could also be due to the occurrence of sibling species of H. aduncum, suggested by Martín-Sánchez et al (1998), as occurs in other anisakids.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations